THE MANUAL OF PROFESSIONAL COMPETENCE OF THE PROSPECTIVE GRADUATES OF MATHEMATIC EDUCATION FACULTY OF ISLAMIC EDUCATION AND TEACHERS TRAINING THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA MEDAN - Mara Samin Lubis; Eka Khairani Hasibuan; Siti Maysarah; Ella Andhany (State Islamic University of North Sumatra Indonesia, 2019)
The purpose of this study is to find out: 1) Feasibility of the professional competence manual for prospective graduates of Mathematics Education at Faculty of Islamic Education and Teachers Training of the State Islamic University of North Sumatra Medan. 2) The student's response to the guidebooks for Professional Competencies in Undergraduate Mathematics Education Department of Faculty of Isalmic Education and Teachers Training of the State Islamic University of North Sumatra Medan. This is Research and Development tye that is using a model developed by Thiagarajan which is a 4 D (Four D) model consisting of 4 stages, called define, design, develop, and disseminate. The results of this study are that the professional competency guideline book for Mathematics Education graduates has met the valid and practical criteria which can be seen from the average recapitulation of the results of the validation team's assessment obtained by 3.43 with good criteria. So that the lattice guidebook is suitable to be used in lecture programs. In general, the students' response to the Mathematics Education student professional competency guidebook book was very positive, which was 87.55%. Keywords: Manual, Professional Competence, Mathematic Education, Faculty of Islamic Education and Teacher Training, UIN of North Sumtra